Utilization Pattern and Determinants of the Utilization of Pregnancy Related Referral Services in Banke District, Nepal - Thu, NM (2016)
Background: Pregnancy complications are often unpredictable and many women in Nepal live far away from where lifesaving care is available. In this context, a functioning referral mechanism is crucial to enable effective management of maternal complications. This study aims to explore utilization pattern and determinants of utilization of pregnancy related referral services, recommendations for improvements to the referral system in Banke District of Nepal. Methods: This was a descriptive observational study in Banke Zonal Hospital. The study period covered three consecutive weeks in May and June 2013. Both quantitative and qualitative methods were applied. Results: Quantitative interviews indicated that 70% of self-referral and 30% of institutional referral are found in this study. Referral patterns are significantly associated with residence of women within in and outside of Banke district, ethnic group of women. Residency in Banke district is significantly related to self referral. Dalit and Terai ethnic groups more likely to have self referral pattern while Janajati cast has similar proportion in both referral types. Among the health facilities which provide birthing services, women delivered at Bheri Zonal hospital was highest (41%) and 25% of mother delivered at first health facilities (birthing centers) of District Public Health Department.75% of institutional deliveries took place in hospitals. The results of document reviews showed that among the institutional deliveries of 2011-2012, 61% of total deliveries in Behri Zonal Hospitals were from Banke district whilst remaining 39% from other districts. Eightfold increment in hospital delivery rate was dramatic change in Banke district from 9.8% 2000 to 80% in 2011/12 compared to 2000. The better services, availability in 24 hour round the clock, shorter distance to travel with ambulance from home to hospital than birthing centers with relatively less costly and less busy were reasons why women preferred hospital. The qualitative interviews revealed the factors which influence the utilization of referral services are financial barriers, traditional beliefs, perception of women pregnancy related complication. Human resources, equipments for facilities, improved quality of health facilities were most commonly suggested by health workers and to improve utilization of birthing centers and to develop referral guide line were suggested by one health worker each. Conclusions: Further research on the health seeking behavior of women without having institutional delivery should be done to generate evidence to ensure safe deliveries of all expected mothers in Banke district and to provide inputs and guidance for referral protocol to avoid exclusion of those mothers in the referral system. Keywords: birthing centers; institutional delivery; referral system; services; utilization.